Degenerate diffusion operators arising in population biology - Epstein, Charles L. (Annals of mathematics studies, 2013)
This book provides the mathematical foundations for the analysis of a class of degenerate elliptic operators defined on manifolds with corners, which arise in a variety of applications such as population genetics, mathematical finance, and economics. The results discussed in this book prove the uniqueness of the solution to the Martingale problem and therefore the existence of the associated Markov process. Charles Epstein and Rafe Mazzeo use an ""integral kernel method"" to develop mathematical foundations for the study of such degenerate elliptic operators and the stochastic proces.